Eight years follow‐up of a patient with triple vessel disease patient complicated with heart failure without invasive intervention for home‐based exercise rehabilitation combined traditional Chinese medicine: A case report. Issue 6 (26th June 2022) - Zhang, Sisi; Zheng, Huiyang; Liu, Xinyu; Meng, Xiaoping
Abstract: We report 8‐year follow‐up of a home‐based exercise rehabilitation program combined traditional Chinese medicine for a patient with triple vessel disease patient complicated with heart failure without invasive intervention. Improvements were observed in all outcomes. Abstract : For this patient with triple vessel disease patient complicated heart failure, we did not perform percutaneous coronary intervention, after applying home‐based cardiac rehabilitation combined with traditional Chinese medicine, the long‐term follow‐up.